2010
DOI: 10.1111/j.1472-765x.2010.02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Lactobacillus sakei and CNC (Staphylococcus xylosus and Kocuria varians) and their influence on proteolytic activity

Abstract: Aims:  To evaluate interactions between Lactobacillus sakei and coagulase negative cocci (CNC) (Staphylococcus xylosus and Kocuria varians) and to investigate the influence of these interactions on their own proteolytic activity. Methods and Results:  Interactions occurring between strains of Lact. sakei and CNC were assessed by spectrophotometric analysis. The growth of 35 strains of Lact. sakei, used as indicators, was compared to that obtained combining the same strains with growing cells or cell‐free super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
(72 reference statements)
2
30
0
Order By: Relevance
“…Bovine serum albumin was used as a standard. Supernatants were stored at −20°C and then were analyzed by SDS-PAGE using an electrophoretic system as described by Tremonte et al (2007, 2010). Bands were visualized using a G250 staining kit (Biorad, Italia).…”
Section: Methodsmentioning
confidence: 99%
“…Bovine serum albumin was used as a standard. Supernatants were stored at −20°C and then were analyzed by SDS-PAGE using an electrophoretic system as described by Tremonte et al (2007, 2010). Bands were visualized using a G250 staining kit (Biorad, Italia).…”
Section: Methodsmentioning
confidence: 99%
“…Useful microorganisms or antimicrobial natural substances are commonly used in the manufacture of various fermented products to ensure a more controllable fermentation, to shorten the ripening, to improve the safety or to enhance the flavor (Tremonte et al, 2007, 2010, 2016a; Sorrentino et al, 2013; Di Luccia et al, 2016). Specifically, in winemaking processes some lactic acid bacteria (LAB) are able to perform the malolactic fermentation (MLF), a desirable transformation occurring by means of the malolactic enzyme, constitutive only in some LAB species naturally selected during the alcoholic fermentation (Lonvaud-Funel, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Leroi and Courcoux [11] demonstrated the stimulation of lactic acid production in Lactobacillus hilgardii when this strain was allowed to grow together with Saccharomyces cerevisiae. Tremonte et al [24] showed that synergistic interaction occurring between L. sakei and two coagulase negative cocci (CNC) ( Staphylococcus xylosus and Kocuria varians ) increased proteolytic activity in these CNC strains.…”
Section: Introductionmentioning
confidence: 99%